1985
DOI: 10.1080/01688638508401242
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and cognitive sequelae following unilateral lesions acquired in early childhood

Abstract: Eight left-hemisphere lesioned children and eight right-hemisphere lesioned children between 18 months and 8 years of age were compared to control subjects on a battery of intelligence and language measures. Both left- and right-lesioned subjects had lower IQ scores than their controls, yet most functioned within the normal range or higher. Lexical comprehension and production were depressed in both subject groups and appeared to be depressed to a greater degree in right-lesioned subjects than in those with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…We may find, for example, that more children with LH damage fall in the risk range on a particular measure than we would expect by chance on a binomial test, while the same is not true for children with RH damage. Conceptually, this is similar to the approach taken in several previous studies of early unilateral brain injury (e.g., Aram et al, 1985;Dennis & Kohn, 1975;, where children in each neurological group were compared with a separate set of normal controls. In the absence of a significant between-group comparison (e.g., a significant difference between LH vs. RH), significant findings using this binomial approach will be regarded as "weak evidence".…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We may find, for example, that more children with LH damage fall in the risk range on a particular measure than we would expect by chance on a binomial test, while the same is not true for children with RH damage. Conceptually, this is similar to the approach taken in several previous studies of early unilateral brain injury (e.g., Aram et al, 1985;Dennis & Kohn, 1975;, where children in each neurological group were compared with a separate set of normal controls. In the absence of a significant between-group comparison (e.g., a significant difference between LH vs. RH), significant findings using this binomial approach will be regarded as "weak evidence".…”
Section: Discussionmentioning
confidence: 82%
“…To be sure, some studies do report differences in the predicted direction, especially for expressive language, and/or for tasks that involve subtle morphosyntactic contrasts (e.g., Aram et al, 1985Aram et al, , 1986Aram et al, , 1987Aram et al, , 1990Dennis, 1980Dennis, , 1988Dennis & Kohn, 1975;Dennis, Lovett, & Wiegel-Crump, 1981;Dennis & Whitaker, 1976, 1977 but see Bishop, 1983). However, these left-hemisphere findings are often complicated by other factors.…”
Section: (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of children with SLI has revealed that the caudate nucleus is smaller in this group than in controls (Jernigan et al, 1991). In addition, lesions of the caudate nucleus in children appear to have a longer term and more deleterious effect on language than some left-hemisphere cortical lesions (Aram et al, 1985). The thalamus may also play a role in rapid auditory processing, as it is an important relay station for sensory inputs (Crosson, 1992).…”
Section: Structural Neuroimaging Studiesmentioning
confidence: 99%
“…Although some differences have been reported during the period in which language is first acquired (Bates et al, 1997;Reilly, Bates, & Marchman, 1998;Thal et al, 1991;Vicari et al, 2000), the vast majority of studies have failed to uncover robust and statistically reliable left/right differences in children who are tested beyond 5-7 years of age. To be sure, a few studies have reported subtle differences between LHD children and their controls, differences that are not observed (or occur in a less specific form) when RHD children are compared to their own, separate group of controls Aram, Ekelman, Rose, & Whitaker, 1985;Ballantyne, Scarvie, & Trauner, 1994-but see Ballantyne & Trauner, 1999;Dennis & Whitaker, 1976Riva, Cazzaniga, Pantaleoni, Milani, & Fedrizzi, 1986). However, as Bishop has pointed out in some insightful methodological reviews (Bishop, 1983(Bishop, , 1997; see also Bates, 1999;Bates & Roe, 2001), those studies that have uncovered hemispheric differences are plagued by methodological limitations, including mixed etiologies and age of onset, small sample size, and the absence of direct comparisons between LHD and RHD children in a single statistical design.…”
mentioning
confidence: 99%